2012
DOI: 10.1063/1.3692328
|View full text |Cite
|
Sign up to set email alerts
|

Accurate quantum wave packet calculations for the F + HCl → Cl + HF reaction on the ground 12A′ potential energy surface

Abstract: We present converged exact quantum wave packet calculations of reaction probabilities, integral cross sections, and thermal rate coefficients for the title reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 20 publications
3
28
0
Order By: Relevance
“…The energetic barrier on this PES is 3.8 kcal mol À1 . The work of Bulut et al 29 shows that the rate constants predicted by calculations with this PES are an order of magnitude smaller than experimental estimates. 16,17 In addition, they concluded that quantum tunneling will not make a significant contribution to the thermal reaction rates.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The energetic barrier on this PES is 3.8 kcal mol À1 . The work of Bulut et al 29 shows that the rate constants predicted by calculations with this PES are an order of magnitude smaller than experimental estimates. 16,17 In addition, they concluded that quantum tunneling will not make a significant contribution to the thermal reaction rates.…”
Section: Discussionmentioning
confidence: 97%
“…We note that the helicity limit of K max = min( J,40) is much larger than the value of 7 used in a recent quantum wave-packet calculation of the total F + HCl reaction cross-sections. 29 Determination of the latter does not require propagation of the wavepacket as far into the product arrangement as is necessary for the determination of final-state resolved crosssections. An accurate description of the wavepacket in the product arrangement in terms of reactant-arrangement rotational functions requires a larger helicity basis.…”
Section: Iiia Details Of Scattering Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[26][27][28] On the a) Authors to whom correspondence should be addressed. Electronic addresses: fengyanwang@fudan.edu.cn; czako@chem.elte.hu; yangmh@ wipm.ac.cn; kliu@pub.iams.sinica.edu.tw; and hguo@unm.edu other hand, there were many theoretical studies of the rotational effect, [29][30][31][32][33][34][35][36][37][38][39][40] although few were concerned with rotation of polyatomic reactants. [41][42][43][44][45] Since the energy gap between rotational states is typically much smaller than that for vibration, the impact of rotational excitation is often greater per unit energy than its vibrational counterpart.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several recent quantum dynamics studies have been devoted to the exploration of rotational effects in bimolecular reactions. 6,[9][10][11][12][13][14][15][16][17][18][19][20][21][22] In this work, we focus on the rotational mode specificity in a prototypical penta-atom reactive system, namely, the H 2 + NH 2 → H + NH 3 reaction. This reaction has been the subject of extensive theoretical investigations.…”
Section: Introductionmentioning
confidence: 99%